An experimentally verified robust backstepping approach for controlling robotic manipulators actuated via brushless DC motors - Saka, Irem; Unver, Sukru; Selim, Erman; Zergeroğlu, Erkan; Tatlıcıoğlu, Enver (Pergamon-Elsevier Science Ltd, 2024)
This work presents the design and the corresponding stability analysis of a robust backstepping controller for robot manipulators driven by brushless DC motors. The overall stability of the mechanical and electrical subsystems is validated via Lyapunov based arguments. The proposed methodology achieves global practical tracking ( i.e. , globally uniformly ultimate boundedness) of the desired joint level trajectories despite the presence of uncertainties associated with the dynamical parameters of the mechanical and the electrical actuation system. Experimental studies performed on an in house built 2 link robotic device actuated via brushless DC motors are presented to illustrate the performance and feasibility of the proposed method.
Keywords: Nonlinear control systems; Robot manipulators; Lyapunov methods; Robust control; Brushless DC